Streptococcus pyogenes Endocarditis Associated With Varicella—Case Report and Review of the Literature - Savoia, Patrizia; Heininger, Ulrich; Buettcher, Michael (Frontiers in Pediatrics, 2019)
Infection with varicella zoster virus (VZV) is usually a benign and self-limiting disease. Serious complications by bacterial pathogens do occur, such as necrotising fasciitis (NF). One of the most important is Streptococcus pyogenes (or Group A Streptococcus, GAS), which colonizes epithelial surfaces, primarily of the throat and skin. In rare instances, varicella may also be associated with S. pyogenes endocarditis. Review of the literature reveals only 18 children with infective endocarditis (IE) caused by GAS since 1942. VZV as antecedent illness was found in five (28%). Fourteen (78%) had no pre-existing cardiac abnormalities. Death occurred in three (17%) children. Infective endocarditis with acute deterioration secondary to rupture of mitral valve chordae tendineae necessitating cardiac surgery has not been reported in the literature yet. We present this rare and instructive paediatric case and the results of a literature search on S. pyogenes endocarditis in children.